Three-Dimensional Hierarchical Porous Structure of PPy/Porous-Graphene to Encapsulate Polysulfides for Lithium/Sulfur Batteries - Yongguang Zhang (Nanomaterials, 2018)
Herein, we demonstrate the fabrication of a three-dimensional (3D) polypyrrole-coated-porous graphene (PPy/PG) composite through in-situ polymerization of pyrrole monomer on PG surface. The PPy/PG displays a 3D hierarchical porous structure and the resulting PPy/PG hybrid serves as a conductive trap to lithium polysulfides enhancing the electrochemical performances. Owing to the superior conductivity and peculiar structure, a high initial discharge capacity of 1020 mAh g−1 and the reversible capacity of 802 mAh g−1 over 200 cycles are obtained for the S/PPy/PG cathode at 0.1 C, remaining the remarkable cyclic stability. In addition, the S/PPy/PG cathodes demonstrate an excellent rate performance exhibiting 477 mAh g−1 at 2 C.